Edukasi Perencanaan RAB pada Rumah Sederhana Menggunakan Software Berbasis Online - Dwi Aneka Kartini; Muhammad Malik Firdhaus; Akbar Putra Nugraha (Institut Teknologi dan Bisnis Semarang, 2025)
This report presents the results of educational activities on planning a Budget Plan (RAB) for the construction of a simple house in the Taktakan area, Cilowong Village, Serang City. The aim of this activity is to increase public understanding of the importance of good budget planning and utilizing online-based software in preparing RAB. This activity includes direct training, interactive discussions, and practice using the software, so that participants can apply the knowledge gained. Situation analysis shows that many people do not understand the RAB, which has the potential to cause budget waste. With this education, it is hoped that people can be more independent in planning house construction, reduce the risk of waste, and improve their quality of life. It is also hoped that this activity will become a model for other regions facing similar challenges.